Breaking Points: Mediating Rupture and Discontinuity within Oksapmin Church Performances, Papua New Guinea - Macdonald, Fraser (Anthropologica, 2019)
Ongoing and increasingly contested debates within the anthropology of Christianity focus on the role of rupture and discontinuity within processes of conversion, arguing that Christians, particularly evangelical and Pentecostal, seek to break with and condemn their indigenous cultural and religious frameworks. Through an analysis of Oksapmin church performances, as well as drawing upon a range of comparative literature, I contribute to this theoretical discussion by advancing a new conceptual model showing that within Christian music and expressive culture there are at least three distinct ways in which converts create discontinuity with their surrounding social and cultural worlds: “resonant” rupture, defined by a continuity of indigenous aesthetic form and a simultaneous change on the level of asserted meaning; “dissonant” rupture, defined as a total opposition to indigenous expressive forms and an embrace of a Western performative repertoire; and “sonant” rupture, a critique of all instrumentation, both traditional and Western, as symbols of worldliness and a strong emphasis upon singing as the purest form of divine communication. I also show how these modes of expressive discontinuity are, first, rooted in particular historical trajectories and, second, may extend to the everyday, non-ritual lives of Christians as well.